Impact of pain, fatigue and dyspnoea on occupational performance in people with advanced cancer: A longitudinal study. (2nd October 2020) - Sampedro Pilegaard, Marc; la Cour, Karen; Brandt, Åse; Lozano-Lozano, Mario; Gregersen Oestergaard, Lisa
Abstract: Background: Pain, fatigue and dyspnoea are symptoms commonly experienced by people with advanced cancer, which may impact on their occupational performance. It is not known whether these symptoms impact their occupational performance over time. Objective: To examine correlation between pain, fatigue and dyspnoea and occupational performance and the impact of such symptoms on occupational performance over time in people with advanced cancer. Material and Methods: A longitudinal study was conducted including 242 participants assessed at baseline and after six and 12 weeks. Spearman's rank-order test and mixed linear models were performed. Results: The correlation between pain, fatigue and dyspnoea and occupational performance at baseline spanned from trivial to moderate (Spearman's rho: −0.004 to 0.34). Only pain had a statistically significant impact on activities of daily living (ADL) motor ability over time ( p  = 0.01). Participants with no pain problems had the largest decrease in ADL motor ability (−0.24 logits (95%-CI: −0.37 to −0.12)), but the observed decrease was not clinically relevant (≥−0.30). Conclusion: Pain, fatigue and dyspnoea did not seem to highly correlate with occupational performance or impact occupational performance over time of people with advanced cancer.